An Empirical Analysis of the Influence of Corporate Social Responsibility on Investment - Huang, Wei Dong; Jin, Shan Yue (International Journal of Psychosocial Rehabilitation, 2020)
This study empirically analyzes the impact of corporate social responsibility on investment using data from listed companies on both the Shanghai Stock Exchange and Shenzhen Stock Exchange from 2010 to 2017 in China. Corporate social responsibility has a positive impact on investment, especially in state-owned enterprises, and the more positive the cash holdings of the company, the greater the positive impact. This study concludes that listed companies should strengthen their emphasis on social responsibility, actively fulfill their social responsibilities, and enhance the scale of investment to achieve a win–win situation.